Juan Seguin, a Hero of Texas - Kerr, Rita (Austin, TX : Eakin Press, 1985)
Juan grew up and married and settled down on a ranchero in San Antonio, but the revolution came and changed his entire life.
Bibliography: p. 53-54.
Keywords: Seguin, Juan Nepomuceno; Soldiers -- Biography -- Texas; Seguin, Juan Nepomuceno, 1806-1890; Seguin, Juan Nepomuceno, 1806-1890; SEGUIN, JUAN; Texas -- History